Hemodynamic and ventilatory responses during exercise in chronic thromboembolic disease - van Kan, Coen; van der Plas, Mart N; Reesink, Herre J; van Steenwijk, Reindert P; Kloek, Jaap J; Tepaske, Robert; Bonta, Peter I; Bresser, Paul (The Journal of thoracic and cardiovascular surgery, 2016)
Patients with chronic thromboembolic disease (CTED) may suffer from exercise intolerance without pulmonary hypertension at rest. Pulmonary endarterectomy (PEA) for symptomatic CTED results in improvement of symptoms and quality of life. Neither the pathophysiology of the exercise limitation nor the underlying mechanisms of the PEA-induced improvement have been studied previously. We studied hemodynamic and ventilatory responses upon exercise in 14 patients with CTED. After 1 year, we studied the underlying physiologic mechanisms of the PEA-induced symptomatic improvement. Cardiopulmonary exercise testing (CPET) was performed during right heart catheterization, and noninvasive CPET was performed 1 year postoperatively. During exercise, we observed abnormal pulmonary vascular responses, that is, a steep mean pulmonary artery pressure/cardiac output (2.7 ± 1.2 mm Hg·min·L(-1)), and low pulmonary vascular compliance (2.8 ± 1.1 mL·mm Hg(-1)); mean pulmonary artery pressure/cardiac output slope correlated with dead-space ventilation (r = 0.586; P = .028) and ventilatory equivalents for carbon dioxide slope (r = .580; P = .030). Postoperatively, the improvement observed in exercise capacity was related to improvements in CPET-derived parameters pointing to restoration of right ventricle stroke volume response (oxygen pulse: 11.7 ± 3.1 to 13.3 ± 3.3; P = .027; heart rate response: 80.9 ± 12.4 to 72.0 ± 5.7; P = .003); and, indicating improved ventilatory efficiency, the ventilatory equivalents for carbon dioxide slope decreased from 38.2 ± 3.6 to 32.8 ± 7.0 (P = .014). Patients with CTED showed an abnormal pulmonary vascular response to exercise and a decreased ventilatory efficiency. Responses after PEA point to restoration of right ventricle stroke volume response and ventilatory efficiency.